1988
DOI: 10.1002/hup.470030206
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quazepam, triazolam, flunitrazepam and placebo, alone and in combination with ethanol, on day‐time sleep, memory, mood and performance

Abstract: Day-time sleep and residual effects of quazepam 15 mg, triazolam 0.25 mg, flunitrazepam I mg, and placebo, alone and in combination with ethanol, were studied using a randomized, double-blind, crossover, single-dose design. Eight healthy volunteers, four male and four female, aged 19-24 years, received each medication in the morning after a 'normal' sleep at home the preceding night.Quazepam and triazolam decreased the sleep onset when compared to placebo. The combination with ethanol did not change these find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Our triazolam data confirm and extend previous pharmacodynamic studies performed according to our experimental paradigm (Baktir et al, 1983;Schlaginhaufen et al, 1984;Wickstrom and Godtlibsen, 1988;Sostmann et al, 1989) by showing a significant effect on all psychomotor tests. Overall, our findings suggest that triazolam, at 0.25 mg single oral dose, behaves as an 'objectively sedative' BZ.…”
supporting
confidence: 94%
See 3 more Smart Citations
“…Our triazolam data confirm and extend previous pharmacodynamic studies performed according to our experimental paradigm (Baktir et al, 1983;Schlaginhaufen et al, 1984;Wickstrom and Godtlibsen, 1988;Sostmann et al, 1989) by showing a significant effect on all psychomotor tests. Overall, our findings suggest that triazolam, at 0.25 mg single oral dose, behaves as an 'objectively sedative' BZ.…”
supporting
confidence: 94%
“…In clinical and electroencephalographic studies, quazepam showed (at an oral dose of 15 mg) effective hypnotic activity and low toxicity (Tietz et al, 1979;Maiman, 1981;Uhthoff and Aggerwall, 1981;Goethe and Kader, 1982;Mendels and Stern, 1983;Winsauer et LEE., 1984;Mendels, 1985). Nevertheless, in two objective studies performed on a small number of healthy volunteers, the same single oral dose of quazepam, when given during the day, had the same effects as placebo on tests of neuromotor performance Wickstrom and Godtlibsen, 1988). It has been postulated that the high hypnotic specificity (which has been suggested to be mainly related to anxiolytic properties) and low central toxicity (measured as sedation and ataxia) of quazepam may result from the property of quazepam and the metabolite 2-oxoquaze-~~ t Author t o whom correspondence should be addressed pam to bind selectively to BZ1 receptors (Iorio et al, 1984;Wamsley et al, 1985).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Neben epidemiologischen Studien tragen vor allem experimentelle Studien dazu bei, mithilfe geeigneter Testverfahren, wie Fahrsimulationstests [25,26], realen Fahrtests [27,28], psychomotorischen [29], kognitiven [29], das Gedächtnis betreffenden [30] und physiologischen Tests (EEG [31,32], Maddox-Wing-Test [5,6], Messung der sakkadischen Augenbewegungen [33]) sowie subjektiven Testverfahren [31] [5,6] Aiming Test -Feinmotorik [41] Amnesietest -Gedächtnis (Amnesie) [41,54] Auditory Reaction Time aRT Einfachreaktionszeit auf auditive Reize [31,41] Aufmerksamkeitsbelastungstest d2 d2 selektive Aufmerksamkeit (Durchstreichtest) [26] Aufmerksamkeits-Prüfgerät APG Vigilanz und geteilte Aufmerksamkeit [26] Card Sorting Test CS psychomotorische Leistung [31,41,46] Choice Reaction Time CRT Wahlreaktionszeit [27,39,40,46,49,52,55,58] Clinical Stabilometric Platform CSP Gleichgewicht und Vigilanz [37] Complex Memory Test CMT Kurz-und Langzeitgedächtnis [40] Continuous Subcritical Tracking Task CTT psychomotorische Koordination [42] Continuous Performance Task CPT Aufmerksamkeit [42] Coordination Test -Koordination [52] Critical Flicker Fusion Frequency CFF Aufmerksamkeit und Vigilanz [27,…”
Section: Introductionunclassified